Strategi Pemasaran Jasa Pendidikan di Institut Dirosat Islamiyah Al-Amien (IDIA) Prenduan, Sumenep Madura 2023. - Qonitah Hafidzah; Moh Wardi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study highlights a unique and interesting phenomenon in the realm of higher education marketing strategy. The Al-Amien Prenduan Islamic University Institute (IDIA) has successfully maintained its sustainability for over 40 years despite offering relatively affordable tuition fees. This research aims to develop a comprehensive marketing strategy for educational services at IDIA, as well as to explore the institution’s contribution to the development of service marketing in Islamic higher education. The study employs a qualitative field research approach, with data collection methods including observation, in-depth interviews, and documentation. The data were analyzed using grounded theory techniques, consisting of open coding, axial coding, and selective coding. To formulate an effective marketing strategy, the research applies the marketing mix theory as a foundational framework. The educational service marketing strategy implemented at IDIA includes the provision of high-quality educational products, price humanization strategies that ensure affordability, selection of strategic campus locations, promotional activities tailored to community needs, human resource development, improvement of facilities and infrastructure, and the enhancement of service delivery systems. These strategies are designed to position IDIA as a competitive Islamic higher education institution. Furthermore, the research reveals the significant contributions of service marketing to IDIA’s growth. These include a steady increase in the number of new student enrollments, higher levels of customer satisfaction, an improved institutional image, and ongoing improvements in educational quality. Overall, this study offers valuable insights into how effective educational service marketing can support the sustainability and competitiveness of Islamic higher education institutions in Indonesia.